2010
DOI: 10.1107/s1600536810042170
|View full text |Cite
|
Sign up to set email alerts
|

2,7-Dimethoxy-1,8-bis(4-phenoxybenzoyl)naphthalene

Abstract: Key indicators: single-crystal X-ray study; T = 193 K; mean (C-C) = 0.002 Å; R factor = 0.036; wR factor = 0.099; data-to-parameter ratio = 13.6.In the title molecule {systematic name: [2,7-dimethoxy-8-(4-phenoxybenzoyl)naphthalen-1-yl](4-phenoxyphenyl)methanone}, C 38 H 28 O 6 , the 4-phenoxybenzoyl units adopt a syn orientation with respect to the naphthalene ring system. The internal benzene rings, A and B, make dihedral angles of 86.72 (5) and 79.22 (5) with the naphthalene ring system. The two terminal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The aroyl groups in these compounds are perpendicularly attached to the naphthalene rings and oriented in opposite directions. On the other hand, X-ray structure of 2,7-dimethoxy-1,8-bis(4-phenoxybenzoyl)naphthalene (Hijikata et al, 2010) having the aroyl groups oriented in the same directions has been also revealed. As a part of our ongoing studies on the molecular structures of this kind of homologous molecules, the X-ray crystal structure of title compound, 1,8-diaroylnaphthalene bearing butoxy groups, is discussed in this article.…”
Section: Sup-1mentioning
confidence: 99%
“…The aroyl groups in these compounds are perpendicularly attached to the naphthalene rings and oriented in opposite directions. On the other hand, X-ray structure of 2,7-dimethoxy-1,8-bis(4-phenoxybenzoyl)naphthalene (Hijikata et al, 2010) having the aroyl groups oriented in the same directions has been also revealed. As a part of our ongoing studies on the molecular structures of this kind of homologous molecules, the X-ray crystal structure of title compound, 1,8-diaroylnaphthalene bearing butoxy groups, is discussed in this article.…”
Section: Sup-1mentioning
confidence: 99%
“…For the electrophilic aromatic aroylation of 2,7-dimethoxynaphthalene giving aroylated naphthalene compounds, see: Okamoto & Yonezawa (2009). For the structures of closely related compounds, see: Hijikata et al (2010); Muto et al (2010); Nakaema et al (2008); Nishijima et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…In these compounds, two aroyl groups tend to attach in nearly perpendicular manner and orient in opposite direction. Recently, the crystal structure of 2,7-dimethoxy-1,8-bis(4-phenoxybenzoyl)naphthalene has been clarified as syn-conformation, where two phenoxybenzoyl groups are oriented in the same direction (Hijikata et al, 2010). As a part of our continuous studies on the molecular structures of homologous aroylated 2,7-dimethoxynaphthalene molecules, the X-ray crystal structure of the title compound, (I), bis(2-naphthoylated) 2,7-dimethoxynaphthalene, is discussed in this article.…”
Section: S1 Commentmentioning
confidence: 99%
“…peri-Aroylated naphthalene compounds thus obtained are proved to have non-coplanarly accumulated aromatic-rings-structure in crystal, i.e., the aroyl groups are twistedly situated to the naphthalene ring core in a perpendicular fashion [7][8][9]. Besides, the two aroyl groups are ordinarily oriented in an opposite direction with a few exceptional compounds bearing unidirectionally-aligned aroyl groups [10,11]. The non-coplanarly congested aromatic rings spatial organization makes the authors imagine that formation of strong π…π stacking interactions should be restricted.…”
Section: Introductionmentioning
confidence: 99%